2019
DOI: 10.2174/1874944501912010094
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Organizational Climate, Organizational Commitment and Job Burnout: Case Study Among Employees of the University of Medical Sciences

Abstract: Background and Objective:Organizational climate and organizational commitment have a tangible effect on organizational performance. This study aims to investigate organizational climate in a university of medical sciences along with organizational commitment and job burnout in the university staff.Methods:This cross-sectional study is carried outviadescriptive-analytical method on 250 employees of Torbat Heydariyeh University of Medical Sciences, Iran in 2016. Data collection tools include standard questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…Because of its closeness to employee positive work attitudes such as job satisfaction, dedication, work efficiency, and employee loyalty, organizational climate has garnered substantial attention from previous and present studies (Bahrami et al, 2016;Jyoti, 2013;Langi et al, 2022;Permarupan et al, 2013;Shanker et al, 2017). An array of past and contemporary studies associated the organizational climate with negative out comes such as intention to leave (Jyoti, 2013;Yousef et al, 2014), job burn out (Dinibutun et al, 2020;Seyyedmoharrami et al, 2019). Whereas , an array of past and contemporary researchers have associated the organizational climate with turnover intentions such as Bracarense et al (2022) conducted in the health industry, a research indicated that organizational atmosphere predicted turnover intentions.…”
Section: Organizational Climate and Turn-over Intentionmentioning
confidence: 99%
“…Because of its closeness to employee positive work attitudes such as job satisfaction, dedication, work efficiency, and employee loyalty, organizational climate has garnered substantial attention from previous and present studies (Bahrami et al, 2016;Jyoti, 2013;Langi et al, 2022;Permarupan et al, 2013;Shanker et al, 2017). An array of past and contemporary studies associated the organizational climate with negative out comes such as intention to leave (Jyoti, 2013;Yousef et al, 2014), job burn out (Dinibutun et al, 2020;Seyyedmoharrami et al, 2019). Whereas , an array of past and contemporary researchers have associated the organizational climate with turnover intentions such as Bracarense et al (2022) conducted in the health industry, a research indicated that organizational atmosphere predicted turnover intentions.…”
Section: Organizational Climate and Turn-over Intentionmentioning
confidence: 99%
“…5 One of the psychological problems during the outbreaks of diseases is job burnout, which causes a lack of energy and vitality. 6 During the COVID-19 outbreak, 2.23%, 4.7%, and 5.57% of society had burnout symptoms in the form of emotional exhaustion, personality decency, and personal inadequacy, respectively, which increased the level of anxiety and stress. 7 These symptoms can also affect people's mental health, even leading to mental disorders such as PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] One of the psychological problems during the outbreaks of diseases is job burnout which causes lack of energy and vitality. [ 4 ] At the time of the outbreak of COVID-19, in the components of emotional exhaustion, personality decency, and personal inadequacy, 2.23%, 4.7%, and 5.57% of the society had burnout symptoms, respectively, which increased the level of anxiety and stress. [ 5 ] Due to the impact of COVID-19 on mental health, public education about the disease is important in order to prevent and control it.…”
Section: Introductionmentioning
confidence: 99%